Nursing pharmacology made incredibly easy - Scott, William N.; McGrath, Deirdre (Wolters Kluwer/Lippincott Williams & Wilkins, 2009)
Explains difficult and complex pharmacology concepts. This text covers fundamentals of pharmacology, including where drugs come from, how they are classified and administered, drugs by pharmacologic class for all body systems, as well as pain medications, and potentially dangerous drug interactions